2020
DOI: 10.1136/bcr-2020-237888
|View full text |Cite
|
Sign up to set email alerts
|

Angioedema, ACE inhibitor and COVID-19

Abstract: SARS-CoV-2, the virus responsible for COVID-19, binds to the ACE2 receptors. ACE2 is thought to counterbalance ACE in the renin-angiotensin system. While presently it is advised that patients should continue to use ACE inhibitors or angiotensin receptor blockers, questions still remain as to whether adverse effects are potentiated by the virus. Here, we report a case of a 57-year-old man, unknowingly with COVID-19, who presented to the emergency department with tongue swelling, shortness of breath and difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…When the medical literature is examined, a variety of dermatologic eruptions thought to be related to COVID-19 has been reported, but angioedema has rarely been reported [5][6][7][8][9][10] . Najafzadeh et al 8 was reported similar case as and suggested that angioedemaas possible early diagnostic indicator of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…When the medical literature is examined, a variety of dermatologic eruptions thought to be related to COVID-19 has been reported, but angioedema has rarely been reported [5][6][7][8][9][10] . Najafzadeh et al 8 was reported similar case as and suggested that angioedemaas possible early diagnostic indicator of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, we have noted several publications associating facial, tongue, eye, and lips swelling with COVID-19; however, none of them made a definitive association with race ( 5 8 ).…”
Section: Recently Published Similar Casesmentioning
confidence: 98%
“…Considering the fact that late-onset angioedema on ACE inhibitors is rarely observed, the cited case report supports the notion on the role of COVID-19 as a contributing factor to angioedema. Tongue swelling in a patient taking benazepril for 4 months, unknowingly with COVID-19, has been also recently reported [ 5 ].…”
mentioning
confidence: 92%
“…On the other hand, it is known that ACE-2 receptor is essential for COVID-19 invasion. Binding the virus to the receptor leads to downregulation of ACE-2 which is one of the enzymes responsible for bradykinin breakdown [ 1 , 4 , 5 ]. Therefore, in the presented case, both ramipril and COVID-19 infection could have contributed to the angioedema by increasing levels of bradykinin.…”
mentioning
confidence: 99%
See 1 more Smart Citation